The choice of parameters for the comparative evaluation of wear resistance of the epoxy composite materials - Полоз, Алексей Юрьевич; Липицкий, Станислав Григорьевич; Кущенко, Сергей Николаевич (Technology audit and production reserves, 2016)
Creating new wear-resistant epoxy composite materials for machine parts and mechanisms subjected to abrasive degradation by the solid particles or by using new components in the applied compositions, it is necessary to establish estimation parameters, which determine the wear and performance of these materials with minimal experimental cost. As an evaluation parameter for such materials in the literature it is proposed to use a quantity of used energy for formation of surface area unit (specific surface energy of the material), because the wear is separated the particles from material surface that lead to formation of a new free surface. In addition, for comparison of the wear resistance of the polymer composites, the ratio of their specific energy surfaces was used taking into account the molecular weight of monomer units of the polymers without accounting an interaction of atoms and groups in the molecules of the polymers as a long-range measure of interacting molecules. The comparative wear evaluation of highly silicon carbide-contained epoxy composite materials that are hardened by industrial polyamines of different nature is done. The evaluation showed the feasibility of the proposed evaluation parameter - the dynamic elasticity modulus of the materials to choose the most effective hardener of the compositions - Epikure F-205, which provides a dynamic elasticity modulus of the silicon carbide-contained composite materials at the level of 2,92 • 1010 N / m2. Production tests were carried out for sand nozzles and drain pipes of the hydrocyclones of developed highly silicon carbide-contained epoxy composite materials. As a result, it was confirmed their high operational durability, for comparative evaluation of which we used the values of dynamic elasticity modules of the materials, exceeding 3-5 times the durability of the same products from the widely used cast iron.